Potential signaling pathways, biomarkers, natural drugs, and chronic myeloid leukemia therapeutics - Alqahtani, Sultan (Frontiers in Pharmacology, 2025)
The Philadelphia chromosome signals BCR-ABL1 migration in myeloid clonal proliferation disorders such as chronic myeloid leukemia (CML). The crucial function of the Musashi2-Numb axis in deciding cell fate and its connection to significant signaling pathways like Hedgehog and Notch, which are necessary for the self-renewal pathways of CML stem cells, will be the subject of future research in this work. For this review, we conducted a PubMed search using the terms Musashi2-Numb, signaling pathways, and leukemia. As a result, we assembled several studies. Tyrosine kinase inhibitors like imatinib can kill and eradicate BCR-ABL1 translocated cells, but they cannot directly target BCR-ABL1 leukemia stem cells. The primary issue is stem cells’ resistance to imatinib therapy. Since leukemia stem cells are thought to be treated by the Musashi2-Numb signaling pathway, a successful therapy approach may involve comprehending and controlling the downstream molecules and signaling pathway of BCR-ABL1 that are important in the survival and self-renewal of leukaemia stem cells. Here, we focused on the generalised perspectives of the drugs that target major signaling proteins and change elements or pathways downstream of BCR-ABL1 can effectively treat chronic leukemia stem cells. There are handful number of proteins such as Musashi2 which have substantial diagnostic use in leukemia treatment and strategy. After going through a number recent develeopments in CML and its therapeutics, I presented here an overview of the latest advancements in CML, natural drugs, biomarkers, potential signaling pathways, and treatment strategies.